PELATIHAN PEMBUATAN SURIMI BASAH DAN SURIMI KERING PADA KELOMPOK PENGOLAH IKAN TUNA DI NEGERI TIAL, KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Bernita Silaban; Johanna Tupan; Esterlina E.E. M. Nanlohy; Sherly Lewerissa (Universitas Mataram, 2023)
ABSTRACT Micro-businesses carried out by tuna processing groups in Tial Country, Salahutu District, Central Maluku Regency are still constrained by the availability of raw materials. Rare and abundant in certain seasons so that it affects the production process. During certain seasons, the fish is stored frozen. Not infrequently when it will be used fish meat is dark and smelly. The resulting processed product is not as expected. The micro businesses that are being carried out are still limited to shredded products, nuggets, meatballs, dragon feet and are produced according to order requirements. This PKM aims to provide information to the public about how to make wet surimi and dry surimi and its application as a fortification agent in fish sticks and cookies. The method used in this community service activity uses lecture, discussion and training methods. The target is the tuna processing group “Mahina Solemata. After being given training, there was an increase in the participants' knowledge from not knowing to knowing. The participants admitted that they felt very helpful with the information provided. According to them, the manufacture of wet surimi and dry surumi can be a solution to overcome the availability of raw materials, guarantee quality uniformity so that production can take place throughout the year. The application of wet surimi and dry surimi into fish sticks and cookies can also provide added value to fish processing fishermen groups in diversifying processed tuna products so that the skills and welfare of the group are increasing.